A new species of Parapinnanema (Nematoda, Chromadoridae) from Dr Theodor Mortensen’s Pacific Expedition 1914–16 with an identification key to the genus - Semprucci, Federica; Sørensen, Martin V. (Zootaxa, 2014)
A new species from the family Chromadoridae is described from samples collected during Dr Mortensen’s Pacific Expedition 1914–16 to Honolulu, Hawaii. Parapinnanema hawaiiensis sp. nov. is characterized by a low c’ ratio and especially by a peculiar complex morphology of the median part of the gubernaculum. An updated and modified key to all the valid species of Parapinnanema is proposed.